Reviewing the impact of Facebook on civic participation: The mediating role of algorithmic curation and platform affordances - Papa, Venetia; Ioannidis, Nikandros (My University, 2023)
Datafication changes variables of our society within the political and cultural realms. In this study, we argue that platform affordances and algorithmic curation can impact users’ civic participation through filtering and classifying users’ online political content. Scholars from various disciplines–among them communication, computational studies, and political science–are working on different concepts in order to understand such effects. What we already know is that users’ civic participation is often mediated by algorithmic curation on the one hand, and by the platform’s built-in logic–often referred as mechanisms of affordances–on the other. Few works are cited across the field pointing out the significance of algorithmic personalization in the making of civic participation. One question that still plagues the research is how the impact of Facebook on civic participation is mediated by algorithmic curation and platform affordances. This paper responds to this need by locating existing scholarship within a common conceptual framework using as a starting point: algorithmic curation, civic participation, and platform affordances. This provides a logical structure that facilitates connections between concepts and disciplines that might otherwise be difficult to discern on an interdisciplinary basis.
Keywords: Affordances; Facebook; Civic participation; Algorithmic curation